Population decline of the cape petrel (Daption capense) on King George Island, South Shetland Islands, Antarctica - Braun, Christina; Esefeld, Jan; Savelieva, Larisa; Peter, Hans-Ulrich (Polar biology, 2021)
The Antarctic and the surrounding Southern Ocean are currently subject to rapid environmental changes and increasing anthropogenic impacts. Seabird populations often reflect those changes and so act as indicators of environmental variability. Their population trends may provide information on a variety of environmental parameters on the scale of years or decades. We therefore provide long-term data on the cape petrel ( Daption capense ) population from a long-term monitoring program on Fildes Peninsula, South Shetland Islands, Maritime Antarctic, an area of considerable human activity. Our data, covering a period of 36 years, indicate some variability, but no clear trend in the number of breeding pairs between the breeding seasons 1985 and 2006. However, beginning in the 2008 season, the population decreased significantly and reached a minimum in the 2020 season. The mean annual decrease between 2008 and 2020 was 10.6%. We discuss possible causes of this strong negative population trend. Anthropogenic disturbance only affects a few breeding sites in the area and is therefore unable, on its own, to explain the consistent population decline at all the breeding sites studied. We think it more likely that reduced food availability was the main cause of the drastic decline in the cape petrel population.